(untitled) (Khairulummah, 2022)
Besides creation of mankind, for his best upbringing and training,Allah almighty has blessed him with parents but with the rapidly advancing age of man, the sdemand of training are also increasing day by day. Especially when the educational age begins and social relations increase, responsibilities of educational institutions also increase to impart education and training. Best period of human life is spent in the educational institutions and with fellow students. The role of educational institutions is imperative in shaping life, ability and to accomplish the mission but it is a pity that today our Institutions are only delivering unspiritual education to our new generation, they are unfamiliar with the name of Islamic training. I will try to review the practices of Islamic training being followed in the Institutions and Their responsibility, so that the situation becomes clear. Besides creation of mankind, for his best upbringing and training, Allah almighty has blessed him with parents but with the rapidly advancing age of man, the demands of training are also increasing day by day. Especially when the educational age begins and social relations increase, responsibilities of educational institutions also increase to impart education and training. Best period of human life is spent in the educational institutions and with fellow students. The role of educational institutions is imperative in shaping life, ability and to accomplish the mission but it is a pity that today our Institutions are only delivering unspiritual education to our new generation, they are unfamiliar with the name of Islamic training. I will try to review the practices of Islamic training being followed in the Institutions and Their responsibility, so that the situation becomes clear.